Spatial and temporal variations of silica in a disturbed tropical river basin - Nather Khan Ibrahim; Firuza Begham Mustafa (Universiti Kebangsaan Malaysia, 2010)
Spatial and temporal variations in silica concentration were determined at various rivers and tributaries in the Linggi River Basin, which has been highly polluted due to urban, industrial and agricultural wastes. The silica content measured as reactive silicate in the whole Linggi River Basin ranged from 1.4 to 26.3 mg/L. A clear seasonal variation in silica was noted especially in the major rivers with higher concentration during dry months and lower concentration during the wet months. The concentration was found to decrease as the water flooded downstream. The large drainage area with granite dominated lithology and high denudation especially in the upper catchment is attributed for high silica content in the water of Linggi River Basin.